Youth developement with refrence to life skills in eastern province of Zambia from 2000- 2010 - Tamilenthi, S; Katongo, Emelda Emma (International Multidisciplinary Research Journal, 2012)
Many youths in eastern province of Zambia are poor because they are not schooling and some have only reached high school level only. Most of the them have been expelled from schools as they could not pay their school fees, they have dropped out of school due to various reasons, they are orphans with no forms of support economically, they are unemployed, even if they have good marks to take them up to the college or university levels they could not make it due to lack of financial support and they are adolescent mothers among other forms of impoverishment. The youths in the province are pervasively conditioned by poverty, the situations of unemployment, economic problems, HIV/AIDS pandemic, gender based violence situations, sexual harassment especially for female youths and girl-children. In these situations, many youths have no possibilities of becoming good citizen, capable and able to plan for their own future lives, to live a happy life in the normality of daily life guaranteed by equal dignity. Empowering the youth with life skills have enabled them to withstand the challenges and demands of their daily life. Life skills have equipped the youth in handling the difficulties of the human life. Youth programs have been carried out in rural and urban areas, in compounds as well as in villages, targeting Christian youths and non-Christian youths, youths in schools, youths who have dropped out of schools, youths in colleges and other learning institutions, youths in streets and in communities. In this study analysed the status of youth development from 2000 to 2010. Based on the analysis report the recommendation and conclusion were made.